Relationship Between Childhood Maltreatment With Levels of Depression On Street Children in Surabaya - Sari, Een Permata; Fithriyah, Izzatul; Djuari, Lilik; Dhira Salsabila (Jurnal Psikiatri Surabaya, 2024)
Introductions: Childhood maltreatment is any form of violence or neglect that occurs against children under the age of 18. Street children are a group that is vulnerable to violence because their activities, for which they spend a lot of time on the streets, make it easier for them to experience violence from both adults and fellow students. One of the impacts can cause mental health disorders, one of which is depression. Objective: Analyze the relationship between childhood maltreatment and levels of depression in street children in Surabaya. Methods: A cross-sectional analytical study was conducted on 43 street children from Surabaya City, East Java, Indonesia. Subjects were selected through two stages, namely using the Children's Depression Inventory (CDI) and the International Child Abuse Screening Tool for Children (ICAST-C) to assess depression and childhood maltreatment. Data analysis using chi-square. Results: The results of the study showed that of the 43 respondents, 18 children experienced childhood maltreatment and 31 children experienced moderate depression. The results of the analysis of the relationship between childhood maltreatment and depression levels showed a p-value of 0.481. Conclusion: Childhood maltreatment is not related to the level of depression in street children in Surabaya.